Antena Susun Berpolarisasi Sirkular dengan Menggunakan Distribusi Daya Dolph Tschebycheff - Citra Zaskia Pratiwi; Achmad Munir (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
This paper discusses the design and realization of circularly polarized array antenna using Dolph Tschebycheff power distribution. The advantages of implementing circular polarization yield the array antenna suitable for outdoor communication system and can minimize the Faraday effect. The Dolph Tschebycheff power distribution is used to suppress the side lobe of array antenna. The proposed array antenna, which is intended to operate at the frequency of 5.3 GHz, consists of five square patch elements with seven diagonal slots upon each element to enhance the bandwidth and to produce the circular polarization. The array antenna is designed and realized using two layers of FR-4 epoxy dielectric substrate with the dimension of 119 mm × 44.1 mm and the thickness of 0.8 mm for each dielectric substrate. Each patch element is fed using a proximity coupling technique excited through a 50 Ω SMA connector. The measurement results show the bandwidth of 720 MHz, the side lobe level of 12.39 dB, the gain of more than 6 dBi around the frequency of 5.3 GHz, and the 3 dB axial ratio bandwidth of 200 MHz. It seems that the realized array antenna could produce wide bandwidth, low side lobe level, and circular polarization, so that it is suitable for WLAN application.